SPECTROGRAPHIC ANALYSIS OF TITANIUM ALLOYS IN PROSTHETIC DENTISTRY - A.S. Utyuzh (Journal of Global Pharma Technology, 2016)
This paper considers changes in the chemical composition of titanium alloys according to the method of their treatment. It investigates the chemical composition of three original samples of titanium alloys, three samples after their casting and three samples after their milling. It is revealed that different methods of alloy handling lead to dissimilar changes in its chemical composition.Keywords: Spectrographic analysis, Titanium, Casting, Milling, Billet.